Caracterização radiográfica ex vivo de biomateriais utilizados para regeneração óssea em mandíbulas de porcos - Corbi, Samara Cruz Tfaile [UNESP] (2012)
Introduction: The radiographic characteristics of a biomaterial, such as its density, may influence the evaluation of the results obtained following its clinical use. Objective: The aim of this study was to evaluate the radiographic density of biomaterials used as bone substitutes, inserted into dental sockets and bone defects in created in the jaws of pigs. The influence of a soft tissue simulator on the results was also evaluated. Material and method: Two and three-millimeter-deep bone defects were created in the pigs mandible and the right first molar extraction socket were used. Commercial samples of five biomaterials were tested: Hydroxyapatite, Lyophilized Bovine Bone, 45S5 bioglass (generic), PerioGlass and β-Tri-Calcium Phosphate, and compared to a positive (mandibular bone) and negative (empty alveolar bone defects) controls. Radiographic images were acquired with and without a 10 mm thick soft-tissue simulator. Result: The results for the extraction sockets showed no differences between the biomaterials and the negative control. For the bone defects, the depth of the defect density influenced the density, both in the negative control (p < 0.01) and biomaterials (p < 0.05) groups. The soft- tissue simulator did not alter the results. Conclusion: The type of the evaluated defect can interfere in the radiographic features presented by each biomaterial, while the simulation of soft tissues was not statistically significant.